A Mall Intercept Survey on Religion and Worldview in the Cape Flats of Cape Town, South Africa - Thomas J. Farrar; Khanyisane A. Falake; Adriel Mebaley; Mandisi D. Moya; Ivor I. Rudolph (Journal for the Study of Religion)
This study analyzes worldviews and religious beliefs and practices in the Cape Flats area of Cape Town, South Africa, using a mall intercept survey of n=513 visitors to five shopping centers. Variables considered included demographic characteristics, measures of religiosity and religious pluralism, participation in religious activities, and supernaturalism (both related and unrelated to a traditional Christian-Abrahamic worldview). The majority (69.4%) of respondents identifies as Christian, though denominational affiliation is very diverse. The other two prevalent religious affiliations are the African Traditional Religion (16.4%) and Islam (11.7%). Only 1.6% of the respondents self-identified as non-religious, a smaller percentage than has been found in research on Cape Town as a whole or South Africa nationally. The degree of self-reported religiosity, participation in religious activities, and belief in supernatural phenomena are all high. Associations between demographic characteristics and religion and worldview variables are analyzed in detail.